2021
DOI: 10.1088/1755-1315/908/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

On frozen chernozem genesis and evolution at lacustrine plains in the southern Vitim plateau (Eastern Siberia, Russia)

Abstract: To clarify the probable role of the stage of the post-lake soil in the evolution of clay-illuvial frozen chernozem the studies were carried out in the southern Vitim plateau of Transbaikalia. The research covers soils in the area of ancient currently dried lakes and the lakeside plain of the Yeravninskaya depression. The obtained data evidence the dissimilarity of parent rocks, as well as radical differences in the soils’ characteristics and properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…Our results showed that soil microbial communities at the Eravna Bazin (Vitim Plateau) were dominated by Actinobacteriota and Alphaproteobacteria, which were partly inconsistent with several studies, which reported that bacterial communities were dominated by Actinobacteriota [30][31][32], Proteobacteria [29,33,34], Bacteroidetes [35] or Proteobacteria, Acidobacteriota and Actinobacteriota [36]. We suppose that these differences are due to the unique conditions of soil formation (mountainous relief, sharply continental climate, permafrost) and the properties of the studied soils, which are formed on the southern border of the permafrost zone of Transbaikalia [3,6,14].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Our results showed that soil microbial communities at the Eravna Bazin (Vitim Plateau) were dominated by Actinobacteriota and Alphaproteobacteria, which were partly inconsistent with several studies, which reported that bacterial communities were dominated by Actinobacteriota [30][31][32], Proteobacteria [29,33,34], Bacteroidetes [35] or Proteobacteria, Acidobacteriota and Actinobacteriota [36]. We suppose that these differences are due to the unique conditions of soil formation (mountainous relief, sharply continental climate, permafrost) and the properties of the studied soils, which are formed on the southern border of the permafrost zone of Transbaikalia [3,6,14].…”
Section: Discussioncontrasting
confidence: 74%
“…Sampling depth and number of samples changed across habitats, resulting in 21 soil samples (Table S1). Samples for molecular genetic studies were selected on the basis of previous morphological and geochemical studies [3,5,6,14]. Soil moisture, temperature and pH were synchronously measured using a mobile measurement system for the coupled monitoring of atmospheric and soil parameters (ASMC, Tomsk, Russia), as well as a pH meter (HM Digital, Seoul, Korea).…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation